Effects of the Junction Functionality and Chain Entanglements in Chemomechanical Behavior of Polyelectrolyte Gels - Lianhua Ma; Qingsheng Yang; Chunhui Yang (Advances in Condensed Matter Physics, 2015)
By considering the functionality of junctions and entanglements of polymer chains for polyelectrolyte gels, a new free energy density function is presented via combining Edwards-Vilgis slip-link model with Flory-Huggins theory. On this basis, the effects of the functionality of network junctions and entanglements of polymer chains are systematically analyzed for free swelling of a cubic polyelectrolyte gel and constrained swelling of a blanket layer of the gel. Analytical results show that the functionality of junctions and chains entanglements plays an important role in the coupled chemomechanical deformation of polyelectrolyte gels.